2019
DOI: 10.1016/j.eneco.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Pollution and economic growth: Evidence from Central and Eastern European countries

Abstract: We investigate the relationships between pollution and growth in eleven Central and Eastern European (CEE) countries. Aggregate results, robust to different estimators and control variables, reveal an increasing nonlinear link between GDP and CO2 for the group of CEE countries. However, at a disaggregated, country-level, the relationship between GDP and CO2 is characterized by much diversity among CEE countries, namely: N-shaped, inverted-N, U-shaped, inverted-U, monotonic, or no statistical link. Thus, despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 47 publications
(63 reference statements)
1
43
0
Order By: Relevance
“…The empirical findings show the existence of the N-shaped EKC hypothesis. Lazăr et al ( 2019 ) confirmed an inverted N and inverted U between climate change mitigation and economic growth in Central and Eastern European countries. Likewise, Chen et al ( 2019 ) considered the EKC hypothesis for sixteen Central and Eastern European countries (CEECs) using the GMM model.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The empirical findings show the existence of the N-shaped EKC hypothesis. Lazăr et al ( 2019 ) confirmed an inverted N and inverted U between climate change mitigation and economic growth in Central and Eastern European countries. Likewise, Chen et al ( 2019 ) considered the EKC hypothesis for sixteen Central and Eastern European countries (CEECs) using the GMM model.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The relationship between CO 2 emissions and economic growth is also divergent in these 7 countries. For instance, Lază et al (2019) found that the effects of the three polynomial terms in GDP were not statistically significant for the Czech Republic, Hungary, and Poland. However, using a quadratic function shows that the effect of the two GDP terms is statistically significant in the Czech Republic and Hungary showing an inverted-U-shaped relationship that confirms the environmental Kuznets curve.…”
Section: Panel Long-run Estimatesmentioning
confidence: 99%
“…Moreover, an N‐shaped relationship is evident for the lower emitting OECD countries in the 10th and 20th quantiles, and that link produces an inverted N‐shaped association between GHG and GDP in the 30th quantile. Lazăr, Minea, and Purcel (2019) study on 11 Central and Eastern European countries using data over the period 1996–2015 also highlights that the association involving GDP and emissions is characterized by considerable diversity (N‐shaped, inverted‐N, U‐shaped, inverted‐U, monotonic, or no statistical link) among the studied economies.…”
Section: Resultsmentioning
confidence: 97%